Polynyas and Tidal Currents in the Canadian Arctic Archipelago - Hannah, Charles G.; Dupont, Frédéric; Dunphy, Michael (ARCTIC, 2009)
A tidal model of the Canadian Arctic Archipelago was used to map the strength of the tidal currents, tidal mixing (h/U3), and the vertical excursion associated with the tidal currents that drive water upslope and downslope. The hot spots in these quantities correspond to the location of many of the small polynyas in the archipelago, supporting the idea that the tidal currents make an important contribution to the dynamics of many of these recurring polynyas. The potential link with tidal mixing means that these locations may have enhanced plankton production in the summer. Un modèle des marées de l’archipel Arctique canadien a servi à mapper la force des courants de marée, le mélange de marée (h/U3) et l’excursion verticale associés aux courants de marée qui poussent l’eau en ascendant et en descendant. Les points chauds de ces quantités correspondent à l’emplacement d’un grand nombre des petites polynies de l’archipel, ce qui vient appuyer l’idée selon laquelle les courants de marée jouent un rôle important dans la dynamique d’un grand nombre de ces polynies récurrentes. Le lien susceptible d’exister avec le mélange de marée implique que la production de plancton à ces emplacements pourrait être rehaussée à l’été.